2018
DOI: 10.18203/2320-6012.ijrms20183235
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude towards epilepsy among pharmacy students from Mumbai university

Abstract: Background: Epilepsy is a chronic disorder of the brain that affects people worldwide. The overall prevalence (3.0-11.9 / 1,000) and incidence (0.2-0.6/1,000) of epilepsy in India are comparable to the rates of high-income countries. The high prevalence of negative attitudes towards epilepsy has been highlighted by several studies. Pharmacy students represent a better-educated section of society regarding drugs and have the potential to create awareness, and influence attitudes towards the disease. Thus, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
0
6
2
Order By: Relevance
“…58% of the participants from the present study believed that epilepsy is a form of mental illness. This percentage is much lower than the study done in Mumbai-India (98%), and higher than that of students in a Malaysian university (39.7%) (16,27) , so our result is confusing since pharmacy students should know that epilepsy is not a mental disease instead, rather it is neurological, for this question we show significant relation between gender (male) and the base answer of the question, where 42.2% of male students said that epilepsy is not a form of mental illness compared with 29.1% of female students of same answer, by comparing with the result of a study from Mumbai university that showed no significant difference between males and females about knowledge about epilepsy (16) .…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…58% of the participants from the present study believed that epilepsy is a form of mental illness. This percentage is much lower than the study done in Mumbai-India (98%), and higher than that of students in a Malaysian university (39.7%) (16,27) , so our result is confusing since pharmacy students should know that epilepsy is not a mental disease instead, rather it is neurological, for this question we show significant relation between gender (male) and the base answer of the question, where 42.2% of male students said that epilepsy is not a form of mental illness compared with 29.1% of female students of same answer, by comparing with the result of a study from Mumbai university that showed no significant difference between males and females about knowledge about epilepsy (16) .…”
Section: Discussioncontrasting
confidence: 70%
“…About 54.6% of the participants of the present study said epilepsy is hereditary, A study done among pharmacy students from Pakistan reported that 70% of the students know the hereditary nature of epilepsy, while other study done in the university of Mumbai showed that all the participants thought epilepsy is not hereditary (16,17) ,in a study done among public in Jordan, the percentage of people who think epilepsy is an inherited disease was 43.5% (29) . These difference could have originated as there was conflicting evidence regarding hereditary nature of epilepsy, but the recent research improve this where the development in genetic technology has led to the identification of an increasing number of genes associated with epilepsy (30) .…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations